Exploring Indian Students’ Perception, Behavioral Intentions, and Motivation for Learning with ChatGPT - Kaur, Sukhmeet; Yadav, Babita; Goel, Divya; Devi, Saloni; Ramachandaran, Sharmila Devi; Kumar, Anuj (Prabandhan: Indian Journal of Management, 2024)
Purpose : The paper aimed to develop an understanding of ChatGPT’s increasing popularity among higher education students for exploring, tailoring, and enriching coursework content. The study determined to explore the factors that affected technology acceptance and usage of ChatGPT. Methodology : The paper identified three predictor variables, namely perceived usefulness (PU), ease of usefulness, and behavioral intentions (BIs) of using the ChatGPT technology as the dependent variable. Further, the perception of the students that motivated them to learn was considered as the independent variable. The study executed 300 structured questionnaires online among management students and functioned as a mixed-method research analysis on SPSS and MAXQDA. Findings : The paper conceded that PU, perceived ease of usefulness, and BI significantly correlated with motivations for learning. The qualitative analysis noticed that the students made their coursework, assignments, and projects easier and more convenient with accurate answers with the support of ChatGPT. Practical Implications : The study is limited to the variables considered for empirical study. We advocated that ChatGPT does not completely replace natural learning techniques such as social interaction, observations, and guidance throughout the journey of education and development. The study produced ethical considerations and inventive viewpoints for future research in educational settings. Originality : Unlike previous research on ChatGPT and education, the present work combined to assess the technical acceptance model with students’ BI and learning motivations for new technology.